Hakikat Sains : Pengertian, Fungsi, dan Penerapan dalam Proses Pembelajaran - Ghina Dhaniyah Salsabil; Winda Sari; Ikmawati Ikmawati; Kurniawan Kurniawan (Universitas Maritim AMNI Semarang, 2024)
Science plays a crucial role in human life as it helps us understand the universe through observation, experimentation, and analysis. In education, science not only teaches scientific concepts but also fosters scientific attitudes and critical thinking skills in students. To make science education more meaningful, interactive, and relevant, a deep understanding of the Nature of Science (NOS) is essential. This study aims to explore the understanding, benefits, and application of scientific concepts in the teaching and learning process to shape students' scientific attitudes. Using a literature review method, this research gathers information from various relevant academic sources. The findings indicate that science encompasses elements of philosophy, sociology, history, and psychology that support scientific understanding. By understanding NOS, students will view science as a process of knowledge discovery, rather than merely a collection of facts. The application of science in education also impacts students' ability to apply knowledge in practical contexts, enhance their analytical skills, and adapt to societal changes.